Visuallyconomic.Com: Kolaborasi Data dan Grafik Visual - Widhyatmoko, Danu (Humaniora, 2014)
Visuallyconomic.com is a website of collaboration between economic information data and visual graphics that present infographic which contains Indonesian economy. Paper began with the history of visuallyconomic.com. Then it discussed the roles undertaken by the visuallyconomic.com. Research used literature study method, and continued with reflective data analysis. By the end of the paper, paper showed a more comprehensive picture about visuallyconomic.com's activities such as a social project as well as the information container of Indonesia’s economic development in the form of infographics.